ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO LIKUIDITAS DAN KINERJA (Studi Kasus pada seluruh Perbankan Syariah di Indonesia) - Estika Intan Annisa; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2017)
This study aims to analyze the effect of liquidity risk on bank’s earning in Indonesia. Liquidity risk in this study is proxied by using factors that can be managed by the bank to avoid the threat of liquidity risk. These factors are deposits, cash reserves, liquidity gap, and NPF.The sample selection using purposive sampling method. Purposive sampling method is a method of sampling based on certain criteria. The sample used in this study are 11 banks. The analysis technique used in this research is multiple linear regression. In addition, the hypothesis test used is the F statistic test and statistical test t. The classical assumption used in this study is normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test.The results of the F test states that the deposits, cash reserves, liquidity gap, and NPF jointly affect the bank’s earning. Results of t-test shows that deposits and cash reserves have positive but no significant effect on bank’s earning. Liquidity gap has a positive and significant effect on bank’s earning. And the last one, NPF has a negative but significant effect on bank’s earning.